Edukasi dan Penerapan Aerobic dan Brisk Walking Exercise pada Lansia dengan Hipertensi di Desa Gunungrejo Singosari - Adila, Yunita; Hasta Baruna, Arys; Vidya Amelia, Ratna (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
An elderly or elderly person is a man or woman who has reached the age of more than 60 years (Ministry of Health of the Republic of Indonesia, 2019). Elderly people have a high risk of experiencing degenerative disorders, one of which is hypertension. Hypertension is an abnormal condition in a person's blood pressure which can affect other organ systems and have the impact of causing other diseases such as stroke and coronary heart disease. One way to prevent hypertension can be done and prevented by doing aerobic exercise. This service activity was carried out in RW 01 Gunungrejo Village with the number of elderly people in the elderly posyandu group this time being 15 elderly respondents. The activities carried out were counseling and demonstration of aerobic exercise and brisk walking exercise. An evaluation was also carried out regarding the activities that had been carried out.